2015
DOI: 10.1097/ruq.0000000000000142
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Introducing Routine Antenatal Ultrasound Services on Reproductive Health Indicators in Mpigi District, Central Uganda

Abstract: The preponderance of global maternal and neonatal deaths occurs in low-resource countries. The risk factors that lead to these deaths are often detectable with ultrasound (US) and potentially preventable. We assessed the impact of performing US scanning during antenatal care (ANC) on reproductive health service utilization in a rural Ugandan district. This pragmatic comparative study was conducted in 2 constituencies of Mpigi district in Uganda. In the 5 intervention sites located in the Mawokota North constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 7 publications
1
47
0
3
Order By: Relevance
“…Other studies have shown that introducing obstetric ultrasound at the lowest level of the healthcare system in a low-resource setting increases ANC attendance and referral of high-risk pregnancies, and can motivate women to give birth at a health facility [46,47]. The participants also wished to decrease the gap between different socio-economic groups in relation to access to obstetric ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that introducing obstetric ultrasound at the lowest level of the healthcare system in a low-resource setting increases ANC attendance and referral of high-risk pregnancies, and can motivate women to give birth at a health facility [46,47]. The participants also wished to decrease the gap between different socio-economic groups in relation to access to obstetric ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…A correct determination of gestational age is needed to distinguish preterm newborns from newborns who are with low birth weight (but not preterm), which is important because the needed interventions may differ [ 9 ]. The regular use of ultrasound scan in the management of pregnancy has dramatically improved the detection of high-risk pregnancies and increased prenatal care attendance although there is no consensus about whether the use of obstetric ultrasound has the ability to decrease maternal and child mortality in low- and middle-income countries [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[15] If applied to the statistics provided by the midwives, this would mean an average of an additional 2-3 obstetrics referrals per midwife per month. The need for increased human resources is also supported by the 2006 World Health Report, which estimated that an additional 1.5 million health care workers would be needed in Africa to meet the health care demands.…”
Section: Discussionmentioning
confidence: 99%